Development of a recombinant adenoviral immunocontraceptive vaccine (Ad-GKT) for use in domestic dogs - Nel, Louis Hendrik (University of Pretoria, 2021)
Dissertation (MSc (Microbiology))--University of Pretoria, 2021.